Hubungan Penerapan Asuhan Keperawatan dengan Kepuasan Pasien di Ruangan Rawat Inap Rumah Sakit Umum Daerah Ogan Ilir Tahun 2024 - Warda Tunisa; Alkhusari; Nila Alfa Fauziah; Ranida Arsi (CV. Creative Tugu Pena, 2024)
The quality of health services in hospitals is currently one thing that is emphasized and even required to be a benchmark for work achievements also has 5 factors that affect patient satisfaction, namely: 1) responsiveness, 2) reliability, 3) assurance, 4) empathy, 5) physical evidence. Nursing care includes: assessment, diagnosis, intervention, impediment, evaluation. With these factors, patients can assess how the nursing services they receive and can perceive whether it is in accordance with what the patient wants or not. The purpose of this study is to obtain an overview of the relationship between the application of nursing care and patient satisfaction in the Inpatient Room of Ogan Ilir Regional General Hospital. This study uses an analytical survey quantitative research design with a cross sectional design approach, which is a research to study the dynamics of correlation between relationships and effects, between independent variables and dependent variables. This research was carried out in June-July 2024 where it was carried out in the PDL Room of Ogan Ilir Hospital with a sample of 96 respondents where the data collection tool was a questionnaire. The results of the study found that there was a relationship between assessment and patient satisfaction with a p-Value of 0.026, a relationship between Diagnosis and patient satisfaction with a p-Value of 0.004, a relationship between intervention and patient satisfaction with a p-Value of 0.017, a relationship between implementation and patient satisfaction with a p-Value of 0.023. there was a relationship between evaluation and patient satisfaction with a p-value of 0.017. The results of this study are expected to improve the quality of service in the aspect of nursing care from assessment, diagnosis, intervention, implementation and evaluation to increase patient satisfaction in the service of hospitalized patients